Validación de la versión Portuguesa de la self-efficacy scale for physical education teacher education major toward children with disabilities (Validation of the Portuguese version of the self-efficacy scale for physical education teacher education major - Campos, Maria João Carvalheiro; Ferreira, José Campos; Morais, Milena; Rodrigues, Graciele (Retos, 2022)
Teniendo en cuenta la relevancia de analizar el proceso de validación y las propiedades psicométricas de los instrumentos de evaluación de autoperceciones y que hasta la fecha no hay ningún cuestionario desarrollado y validado en Portugués en la autoeficacia de los profesores con respecto a la inclusión de los estudiantes com deficiência en las clases de educación física, este estudio tuvo como objetivo analizar las propiedades psicométricas y la estructura fatorial de la versión en portugués de la Physical Education Teacher Education Majors towards Children with Disabilities (SE-PETE-D) (Block et al, 2013) para Escala de Autoeficácia na Educação Física Inclusiva (EAE-EFI). Participaram 222 profesores de educación física que trabajan en el 1º, 2º y 3º ciclos de la Educación Básica y Secundaria de Portugal, 127 hombres y 95 mujeres, con edades comprendidas entre los 21 y 60 años (M=36.39. DP=13.15). La escala mostró valores elevados de consistencia interna (α=.96 para la escala total), con valores entre os .64 e .78 para lo teste re-teste. Sin embargo, los valores de corte asociados a la bondad de los índices del modelo teórico (NFI, CFI, RMSEA) presentaron algunas limitaciones por lo que serán necesarios estudios más profundos para viabilizar el ajuste del modelo. La versión portuguesa de la SE-PETE-D muestra buenos resultados en cuanto a su consistencia interna y su estabilidad temporal, y puede ser una importante herramienta de evaluación para analizar la autoeficacia de los profesores de EF y futuros profesores de EF hacia la inclusión de estudiantes con discapacidades en países de habla portuguesa. Abstract. Considering the pertinence in analysing the validation process and the psychometric properties of self-perceptions assessment instruments and taking into account that to date there is no survey developed and validated in the Portuguese language on the self-efficacy of teachers toward the inclusion of students with disabilities, the purpose of this study was to analyse the psychometric properties and the factor structure of the Portuguese version of the Self-Efficacy Scale for Physical Education Teacher Education Majors towards Children with Disabilities (SE-PETE-D) (Block et al., 2013), called the Escala de Autoeficácia na Educação Física Inclusiva (EAE-EFI). The participants were 222 Physical Education teachers from elementary, middle and secondary schools in Portugal, 127 males and 95 females, aged between 21 and 60 years (M=36.39, SD=13.15). Results showed high values ​​of internal consistency (α=.96 for the global scale), with values between .64 e .78 for the test re-test. However, a number of the cut-off values ​​associated with the goodness of the fit indexes of the theoretical model (NFI, CFI, RMSEA) presented certain restraints. The Portuguese version of the SE-PETE-D shows good results with regard to its internal consistency and its temporal stability, and can be an important assessment tool to analyze the self-efficacy of PE teachers and future PE teachers toward the inclusion of students with disabilities in Portuguese speaking countries.